DISCURSIVE AND COMPENSATORY MEANS (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article examines discursive and compensatory means in political discourse, focusing on their functions, classifications, andcommunicative impact. The study explores how various linguistic and rhetorical strategies shape political messages, influencepublic perception, and contribute to the construction of ideological narratives. By analyzing contemporary political texts, theresearch identifies key mechanisms used to manage political communication effectively. The findings highlight the role ofdiscursive and compensatory techniques in shaping political debates, enhancing persuasion, and mitigating communicativefailures.